2023
DOI: 10.1159/000530123
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Signs of Neuropathy and Self-Reported Substance Use Disorder for Nitrous Oxide in Patients Intoxicated with Nitrous Oxide

Abstract: <b><i>Introduction:</i></b> The number of patients with excessive nitrous oxide (N<sub>2</sub>O) use and neurological disorders has been rising, indicating an addictive potential of N<sub>2</sub>O. We studied the incidence of self-reported substance use disorder (SUD)-related symptoms, signs of neuropathy, and the patterns of use in N<sub>2</sub>O-intoxicated patients. <b><i>Methods:</i></b> The Dutch Poisons Information Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Criterion 1: Taking N 2 O in larger amounts or over a longer period than intended A systematic review of case reports of heavy N 2 O use showed that 98% (of 61) of individuals reported using N 2 O in larger amounts or for longer durations than intended [7]. Further evidence for the presence of this symptom is provided by a survey conducted by Nugteren-Van Lonkhuyzen et al [8] as part of a prospective observational cohort study on neuropathy and self-reported SUD in Dutch patients intoxicated with N 2 O. Nine of 10 users reported using N 2 O in larger amounts or for longer durations than intended.…”
Section: Loss Of Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…Criterion 1: Taking N 2 O in larger amounts or over a longer period than intended A systematic review of case reports of heavy N 2 O use showed that 98% (of 61) of individuals reported using N 2 O in larger amounts or for longer durations than intended [7]. Further evidence for the presence of this symptom is provided by a survey conducted by Nugteren-Van Lonkhuyzen et al [8] as part of a prospective observational cohort study on neuropathy and self-reported SUD in Dutch patients intoxicated with N 2 O. Nine of 10 users reported using N 2 O in larger amounts or for longer durations than intended.…”
Section: Loss Of Controlmentioning
confidence: 99%
“…Two studies specifically investigated the prevalence of unsuccessful efforts to cut down or stop N 2 O use, rendering contradicting results. Although Nugteren-Van Lonkhuyzen et al [8] concluded that 8 of 10 heavy N 2 O users reported having tried to control their use unsuccessfully, Fidalgo et al [7] found that only two of 59 case reports documented evidence for criterion 2.…”
Section: Loss Of Controlmentioning
confidence: 99%
See 3 more Smart Citations